Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/horticulturae6040091
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Fruit Size and Phenolic and Enzymatic Composition of Avocado Byproducts (Persea americana Mill.): The Importance for Biorefinery Applications

Abstract: Avocado byproducts are a rich source of health-promoting biomolecules. The purpose of this work is to study three groups of statistically different avocado fruit sizes (Persea americana Mill.) (small (S), medium (M), and large (L)), and their relationship with total phenolic and flavonoid contents (TPC and TFC, respectively), DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging capacity and individual phenolics, and the activities of phenylalanine ammonia-lyase (PAL), chalcone synthase (CHS), and polyphenol oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The study reported higher TPC, TFC, and antioxidant and enzymatic activities in avocado peel extract from the small size group, while these parameters were significantly lower in the other groups. These results suggest avocado by-products' suitability for biorefinery applications [13].…”
Section: Introductionmentioning
confidence: 74%
“…The study reported higher TPC, TFC, and antioxidant and enzymatic activities in avocado peel extract from the small size group, while these parameters were significantly lower in the other groups. These results suggest avocado by-products' suitability for biorefinery applications [13].…”
Section: Introductionmentioning
confidence: 74%
“…Araujo et al [61] identified 15 major compounds in the peel, such as 11 procyanidins, dimers and trimers in different isomer shapes. Trujillo-Mayol et al [31] identified that the main flavonoids present in avocado peel were epicatechin (0.02 mg/g) and hesperidin (0.01 mg/g). In addition, there were non-flavonoid phenolics such as caffeic acid (0.2 mg/g), coumaric acid (0.1 mg/g) and ferulic acid (0.01 mg/g) [62].…”
Section: Avocadomentioning
confidence: 99%
“…This fruit is also considered very valuable because it has a complete nutritional content associated with many health benefits due to the high levels of unsaturated fatty acids, minerals, fiber, proteins, vitamins and phenolic compounds [102,152]. This high content of phenolic compounds confers to avocado numerous biological activities, including antifungal, antibacterial, antidiabetic, antihypertensive, anti-inflammatory, anticancer, and hypo-cholesterolemic properties [31,61,103,153,154]. Ervianingsih et al [155] used avocado seed waste in biscuits as an alternative food for people with diabetes, because studies demonstrated that the flavonoids could reduce blood glucose levels through glucose absorption or by increasing insulin secretion, can stimulate glucose absorption in peripheral tissues, and regulate the work of enzymes involved in carbohydrate metabolic pathways.…”
Section: Avocadomentioning
confidence: 99%
See 1 more Smart Citation
“…The peels from avocado Hass ( Persea americana Mill) were obtained from small-sized avocado fruits from the north part of Chile, according to a previous characterization [ 85 ]. Then, an hydroethanolic avocado crude extract was obtained by the optimal condition of the ultrasound–microwave combined method developed in our previous work [ 3 ].…”
Section: Methodsmentioning
confidence: 99%